Improving the efficiency of small animal 3D‐printed compensator IMRT with beamlet intensity total variation regularization. Issue 8 (6th June 2022) - Liu, Xinmin; Van Slyke, Alexander L.; Pearson, Erik; Shoniyozov, Khayrullo; Redler, Gage; Wiersma, Rodney D.
Abstract: Purpose: There is growing interest in the use of modern 3D printing technology to implement intensity‐modulated radiation therapy (IMRT) on the preclinical scale that is analogous to clinical IMRT. However, current 3D‐printed IMRT methods suffer from complex modulation patterns leading to long delivery times, excess filament usage, and less accurate compensator fabrication. In this work, we have developed a total variation regularization (TVR) approach to address these issues. Methods: TVR‐IMRT was used to optimize the beamlet intensity map, which was then converted to a thickness of the corresponding compensator attenuation region in copper‐doped polylactic acid (PLA) filament. IMRT and TVR‐IMRT heart and lung plans were generated for two different mice using three, five, or seven gantry angles. The total compensator thickness, total variation of compensator beamlet thicknesses, total variation of beamlet intensities, and exposure time were compared. The individual field doses and composite dose were delivered to film for one plan and gamma analysis was performed. Results: In total, 12 mice heart and lung plans were generated for both IMRT and TVR‐IMRT cases. Across all cases, it was found that TVR‐IMRT reduced the total variation of compensator beamlet thicknesses and beamlet intensities by 54 ± 4 % $54± 4%$ and 50 ± 3 % $50± 3%$ on average when compared to standard 3D‐printed compensator IMRT. On average, the total mass of compensator material consumed and radiation beam‐on time were reduced by 45 ± 6 % $45± 6%$ and 24 ± 4 % $24± 4%$, respectively, whereas dose metrics remained comparable. Heart plan compensators were printed and delivered to film and subsequent gamma analysis performed for each of the single fields as well as the composite dose. For the composite delivery, a passing rate of 89.1% for IMRT and 95.4% for TVR‐IMRT was achieved for a 3 % / 0.3 $3%/0.3$ mm criterion. Conclusions: TVR can be applied to small animal IMRT beamlet intensities to produce fluence maps and subsequent 3D‐printed compensator patterns with significantly less complexity while still maintaining similar dose conformity to traditional IMRT. This can simplify/accelerate the 3D printing process, reduce the amount of filament required, and reduce overall beam‐on time to deliver a plan.